3D Master Toothguide Is Adequate to Subjective Shade Selection? - Cristina Gómez-Polo; Miguel Gómez-Polo; Norberto Quispe López; Maria Portillo Muñoz; Javier Montero (Medicina, 2022)
Background and Objectives: To study the validity and the degree of representability of the toothguide 3D Master, with 26 physically shade tabs, on the natural tooth colour on a sample of the Spanish population. Materials and Methods: Natural tooth colour was measured in a sample of 1361 Spanish participants of both genders distributed within an age range of 18 and 89 years of age. The colour coordinates were calculated and the frequency of the 26 physically shade tabs of the toothguide as well as the “intermediate shades” (without physical representation in toothguide) through the Easyshade Compact (Vita-Zahnfabrik) spectrophotometer using the 3D Master System nomenclature. The colour differences between the “intermediate shades” were calculated using the Euclidean formula (ΔEab*). The program used for the present descriptive statistical analysis of the results was SAS 9.1.3. Results: A total of 49 “intermediate shades” were registered in 816 participants (60%). The colour coordinates of the 49 ‘intermediate shades’ cover colour coordinates ranging from 0M1.5 (L* 100.0, C* 7.70, h* 112.2) to 5M2.5 (L* 56.8, C* 35.8, h* 78.5). Not all possible 3D Master System’s “intermediate shades” were registered in the population studied. 82.4% of the colour differences among the “intermediate shades” were clinically unacceptable (ΔEab* ≥ 5.5 units). Conclusions: Only 40% of the population studied presented a natural tooth colour belonging to the 3D Master Toothguide’s physical shade tabs.